Phenological study of Caesalpinia ebano (H. Karst) in the middle Valley of Sinú, Colombia - Falla-Guzman, Cindy Katherine (2023)
The dry forests sections of the Caribbean region in Colombia have been disturbed due to the expansion of the agricultural frontier, among other anthropic activities, generating pressure on native plant species of this ecosystem and biodiversity loss threat. Information of the plant species biological processes guides management for their conservation. Therefore, this study evaluated phenological process of the Caesalpinia ebano in dry forest of  the Caribbean Region in Colombia. Scattered trees were selected and phenological records were collected for one year. Five stages or phenophases were evaluated: flowering buds, green fruits (at initial stages and fully developed), ripe fruits (reddish), leaf buds and mature leaves. It was found that during the sampling time the species showed two reproductive peaks, being the second peak where flowering buds, fully developed green fruits, and ripe fruits reached their maximum values with 53.3 %, 80 % and 65 % respectively. Regarding the  vegetative phases (mature leaves and leaf flush), highest records of mature leaves were observed in the first quarter of the year, which corresponded to driest months. In May, we observed the highest percentage of leaf flush (i.e., 86.7 %) and this corresponds to the peak of rainfall throughout the year. The phenological phases were influenced mainly by the climatic variables, precipitation, and temperature.